Teleangiectasia hereditaria haemorrhagica - syndrom Osler-Weber-Rendu. Popis případu a zkušeností s léčbou - Adam, Z; Chlupová, G; Neumann, A; Jakubcová, B; Simonides, J; Adamová, Z; König, J; Krupa, P; Szturz, P; Pour, L; Krejčí, M; Hájek, R; et al. (Vnitrni lekarstvi, 2012)
Hereditary haemorrhagic telangiectasy is an inborn disease with autosomal dominant transmission. Nose bleeding usually occurs during the 2nd decade of life as the first sign of the disease. Later, during the 3rd or 4th decade of life, typical subtle, pinhead-sized (1-2 mm in diameter) vascular arteriovenous malformations occur. These are usually found on the oral mucosa and in the stomach and small intestine. During later stages of the disease, nose as well as gastrointestinal bleeding causes severe anaemia requiring transfusions. Advanced stages of hereditary hemorrhagic telangiectasy are associated with a development of ateriovenous vascular malformations in the liver, lungs and possibly the brain. Vascular ateriovenous malformations in the liver cause hyperkinetic circulation that may lead to heart failure. Blood within the pulmonary ateriovenous malformations bypasses filtration in the pulmonary capillary circulation and thus infected microtrombi may pass from the inferior vena cava to, for example, the brain. At first, local treatment - stopping epistaxis - is used. Symptomatic embolisation treatment and, sometimes, liver transplantation are used in advanced forms of the disease with anaemisation, despite iron substitution, and clinically significant ateriovenous malformations. Angiogenesis-inhibiting substances have been shown effective in patients with an advanced disease. Older clinical studies confirmed benefits of combined oestrogen-progesterone treatment, later also treatment with raloxifene or antioestrogens. Many post-2000 publications showed thalidomide and bevacizumab to be effective in this indication. Treatment with bevacizumab has led not only to increased haemoglobin concentrations but, through regression of ateriovenous malformations, provided control of hyperkinetic circulation. Discussion section provides an overview of treatment modalities. The main text describes a case of a 56 years old female patient with hypochromic anaemia despite maximum oral iron substitution. The patient lost blood through repeated epistaxes as well as continuous mild bleeding into gastrointestinal tract. The patient also had confirmed large ateriovenous malformations in the liver. Interferon alpha was used as the first line of treatment. The patient unexpectedly developed fast and pronounced myelosuppression. The number of neutrophils fell down from 1.15 x 109/l to 0.6 × 109/l as soon as after 3 injections of interferon alpha at a starting dose of 1.5 million units 3 times a week. Therefore, interferon alpha was discontinued. Blood count returned to normal following interferon discontinuation. The patient was started on thalidomide in December 2011. The patient reported lower incidence of epistaxes and smaller blood loss than before treatment as soon as during the first month of therapy. Regular administration of thalidomide reduced intensity and frequency of epistaxes in this patient.
Keywords: lidé; Telangiectasia, Hereditary Hemorrhagic; Middle Aged; hereditární hemoragická teleangiektazie; ženské pohlaví; lidé středního věku; Humans; Female